Youth agency in times of crisis: Exploring education and conflict in Mali through participatory visual approaches with youth - Mitchell, Claudia; Lussier, Kattie; Keita, Fatoumata (Frontiers in Education, 2022)
Education in Mali is constrained by a multi-dimensional crisis that restricts education and makes life difficult. Young people are particularly affected. In this article, we use the preliminary findings of the Participatory Research on Education and Agency in Mali (PREAM) project that was implemented in the conflict-affected regions of Mopti and Segou, to discuss youth agency in situations of crisis and how participatory visual methods can be used both as a way of ascertaining adolescents’ perception of their agency and also to contribute to the development of youth agency. More specifically, we use data from six workshops using participatory visual methods (PVMs) to illustrate that young people have something valuable to say about education, agency, and conflict and that PVMs can be an effective way of engaging adolescents in dealing with such topics. Preliminary findings from the research suggest that although participating young people are in an asymmetrical position in relation to power with the adults around them, they nonetheless have a good understanding of their situation and demonstrate agentic behavior that is both adaptative and projective. Girls illustrated how generational order from child to grandmother and gender social norms can constrain agency. At the same time, they used their agency to expose and contest, in the cellphilms they produced, the unfair division of labor in their society. During the workshops, young people were eager to share their stories and wanted their artwork to communicate their concerns to the adults around them. In this article, we argue that it is important for adolescents in Mali to have a voice on questions of education and agency and we discuss why education actors and policy makers should pay attention to the perspectives of young people even (and especially) in times of crisis.